Physical Processes Dictate Early Biogeochemical Dynamics of Soil Pyrogenic Organic Matter in a Subtropical Forest Ecosystem - Stuart, Jason M.; Anderson, Russell; Lazzarino, Patrick; Kuehn, Kevin A.; Harvey, Omar R. (Frontiers in Earth Science, 2018)
Quantifying links between pyOM dynamics, environmental factors and processes is central to predicting ecosystem function and response to future perturbations. In this study, changes in carbon (TC), nitrogen (TN) , pH and relative recalcitrance (R50) for pine- and cordgrass-derived pyOM were measured at 3-6 weeks intervals throughout the first year of burial in the soil. Objectives were to 1) identify key environmental factors and processes driving early-stage pyOM dynamics, and 2) develop quantitative relationships between environmental factors and changes in pyOM properties. The study was conducted in sandy soils of a forested ecosystem in the Longleaf pine range, US with a focus on links between changes in pyOM properties, fire history (FH), cumulative precipitation (Pcum), average temperature (Tavg) and soil residence time (SRT). Pcum, SRT and Tavg were the main factors controlling TC and TN accounting for 77-91% and 64-96% of their respective variability. Fire history, along with Pcum, SRT and Tavg, exhibited significant controlling effects on pyOM, pH and R50 - accounting for 48-91% and 88-93% of respective variability. Volatilization of volatiles and leaching of water-soluble components (in summer) and the sorption of exogenous organic matter (fall through spring) were most plausibly controlling pyOM dynamics in this study. Overall, our results point to climatic and land management factors and physicochemical process as the main drivers of pyOM dynamics in the pine ecosystems of the Southeastern US.